Adorno versus Lyotard Moderne und postmoderne Ästhetik - Kogler, Susanne (Verlag Karl Alber, 2014)
It is well known that Theodor W. Adorno's aesthetic theory is grounded in his profound musical knowledge. The importance of music for Jean-François Lyotard, however, has not been adequately recognized until today; neither has the fact that Lyotard was strongly influenced by Adorno. Tracing back the development of Lyotard's thought from his "pagan" beginnings to his late conception of an informal art, the book intends to initiate an adequate reception of Lyotard's œuvre from a musicological viewpoint. Moreover, as a first comprehensive comparison of Lyotard's and Adorno's theories on art, the study contributes to the exploration of Critical Theory's reception in France.